Child Disability and Parental Well-Being - Blacher, J; McCulloch, A; Llewellyn, G; Hatton, C; Graham, H; Emerson, E (My University, 2007)
Though it is known that mothers of disabled children experience lower well-being than parents of non-disabled children, there have been few large scale, controlled studies. To address this, the authors examined data from two longitudinal samples, the 'Growing Up in Australia: the Longitudinal Study of Australian Children' (LSAC), and the 'Millennium Cohort Study' from the UK. They studied the relationship between child disability and parental mental health, and associated risk factors. This presentation outlines the authors' findings, and features slides on the key measures, maternal distress with children at different age groups, deprivation as a correlate, predictors of maternal distress, and predictors of change on distress levels.
Keywords: Children -- Disabled; Children; Health; Health -- Wellbeing; Health and wellbeing; Children; Health; Disabled; Wellbeing; Health and wellbeing